100% Intensity of Training on Body Weight Fluctuations Before and After Exercise - touvan Juni samodra (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
This study aimed to prove the effect of 100% exercise intensity on weight gain before and after exercise. This research is motivated by the efforts made by people to achieve the ideal body weight. One of the efforts made is by doing exercises. Proper practice is essential. The quality of the exercise is indicated by the intensity of the exercise performed. The study used experimental methods. The research sample was eight students—measurement of body weight before and after exercise. Perform using 100% intensity circuit training based on maximal tests. Descriptive statistics analyzed data. The results showed that they always experience an average weight loss of 2.8. Based on these results, it can reference that circuit training with 100% load could be used to lose weight. Recommendations, for maximum results, it is necessary to record macro nutritional intake, to know a proper diet for weight loss purposes. Key words: overweight, obesity, BMI, circuit training, maximul load